Evaluation Study on Rajiv Gandhi Gramin Vidyutikaran Yojana (RGGVY) - Planning Commission (Planning Commission)
Energy use and development of an economy is highly correlated. Considering this, the Indian planners and policy makers had taken conscious decision to provide energy to rural sector through several rural electrification programmes undertaken in various plans. The latest in the series is the Rajiv Gandhi Grameen Vidyutikaran Yojana (RGGVY) being implemented in Indian states mostly to benefits households below the ""poverty line” through a free connection but chargeable consumption of power.
Programme Evaluation Organisation Planning Commision New Delhi